K(ATP) Channel Openers Inhibit Lymphatic Contractions and Lymph Flow as a Possible Mechanism of Peripheral Edema - Garner, Brittney R. (J Pharmacol Exp Ther, 2021)
Pharmacological openers of ATP-sensitive potassium (K(ATP)) channels are effective antihypertensive agents, but off-target effects, including severe peripheral edema, limit their clinical usefulness. It is presumed that the arterial dilation induced by K(ATP) channel openers (KCOs) increases capillary pressure to promote filtration edema. However, K(ATP) channels also are expressed by lymphatic muscle cells (LMCs), raising the possibility that KCOs also attenuate lymph flow to increase interstitial fluid. The present study explored the effect of KCOs on lymphatic contractile function and lymph flow. In isolated rat mesenteric lymph vessels (LVs), the prototypic K(ATP) channel opener cromakalim (0.01–3 µmol/l) progressively inhibited rhythmic contractions and calculated intraluminal flow. Minoxidil sulfate and diazoxide (0.01–100 µmol/l) had similar effects at clinically relevant plasma concentrations. High-speed in vivo imaging of the rat mesenteric lymphatic circulation revealed that superfusion of LVs with cromakalim and minoxidil sulfate (0.01–10 µmol/l) maximally decreased lymph flow in vivo by 38.4% and 27.4%, respectively. Real-time polymerase chain reaction and flow cytometry identified the abundant K(ATP) channel subunits in LMCs as the pore-forming Kir6.1/6.2 and regulatory sulfonylurea receptor 2 subunits. Patch-clamp studies detected cromakalim-elicited unitary K(+) currents in cell-attached patches of LMCs with a single-channel conductance of 46.4 pS, which is a property consistent with Kir6.1/6.2 tetrameric channels. Addition of minoxidil sulfate and diazoxide elicited unitary currents of similar amplitude. Collectively, our findings indicate that KCOs attenuate lymph flow at clinically relevant plasma concentrations as a potential contributing mechanism to peripheral edema. SIGNIFICANCE STATEMENT: ATP-sensitive potassium (K(ATP)) channel openers (KCOs) are potent antihypertensive medications, but off-target effects, including severe peripheral edema, limit their clinical use. Here, we demonstrate that KCOs impair the rhythmic contractions of lymph vessels and attenuate lymph flow, which may promote edema formation. Our finding that the K(ATP) channels in lymphatic muscle cells may be unique from their counterparts in arterial muscle implies that designing arterial-selective KCOs may avoid activation of lymphatic K(ATP) channels and peripheral edema.